INHIBITION OF CRYPTOSPORIDIUM PARVUM PYRUVATE KINASE (CPPYK) THROUGH COMPUTATIONAL DRUG REPURPOSING (The Research of Medical Science Review, 2025)
Background: Cryptosporidiosis is a waterborne neglected tropical parasitic disease caused by an apicomplexan parasite, Cryptosporidium parvum. The parasite poses significant therapeutic challenges due to limited treatment options and emerging resistance. So, research into alternative treatments is necessary. Developing new drugs is expensive and time consuming. Drug repurposing is a good alternative, and this study targets the Cryptosporidium parvum’s Pyruvate kinase (CpPyk) using this approach. Cryptosporidium parvum uses glycolysis for energy production as it lacks Krebs cycle. CpPyk with its unique structure and function is the key enzyme in the glycolytic pathway and a good target for drug docking. Methods: 100 FDA approved drugs were obtained from Chemspider and docked with CpPyk retrieved from Uniprot, using PatchDock online server. LigandProtein interactions were visualized using LigPlot+. Results: Top 3 drugs with maximum interactions are ceftaroline, streptomycin and ritonavir. These drugs showed covalent and hydrogen bonds as well as hydrophobic interactions with different amino acids of CpPyk. Conclusion: In this study, the drug repurposing approach was used to inhibit Cryptosporidium parvum pyruvate kinase (CpPyk). Ceftaroline, streptomycin and ritonavir showed different types of molecular interactions with CpPyk which are enough to change its conformation and alter its function which is vital for the parasite. With more in vitro and in vivo testing these drugs can be used as alternative treatment for cryptosporidiosis.